Osteopontin activates retinal microglia causing retinal ganglion cells loss via p38 MAPK signaling pathway in glaucoma. Issue 3 (9th February 2021) - Yu, Huan; Zhong, Huimin; Li, Na; Chen, Kaizhe; Chen, Junjue; Sun, Jun; Xu, Lili; Wang, Jing; Zhang, Mingui; Liu, Xiaohong; Deng, Lianfu; Huang, Ping; et al.
Abstract: Microglia activation and release of pro‐inflammatory cytokines have been closely linked to glaucoma. However, the mechanisms that initiate these pathways remain unclear. Here, we investigated the role of a pro‐inflammatory cytokine––osteopontin (OPN), in retinal microglia activation process along with the underlying mechanisms in glaucoma. A rat chronic ocular hypertension (COH) model was established presenting an increase in retinal OPN level and activation of microglia. Primary microglia cells were isolated and cultured under a pressure culture system showing heightened expressions of microglia‐derived OPN with changes in inflammatory factors (TNF‐α, IL‐1β, and IL‐6). OPN and OPN neutralizing antibody (Anti‐OPN) interventions were both applied systems for comparison, and cross‐referenced with OPN knockdown in vitro. JAK/STAT, NF‐κB, ERK1/2, and p38 MAPK, recognized as the primary signaling pathways related to microglia activation, were then screened on whether they can facilitate OPN to act on microglia and their impact on specific inhibitors. Thereafter, retrograde labeling of retinal ganglion cells (RGCs) and flash visual evoked potentials (F‐VEP) were used to investigate neuron protection in context of each blockade. Results suggest that OPN is able to enhance the proliferation and activation of retinal microglia in experimental glaucoma which may play a role in the glaucomatous optic neuropathy, and contribute to the eventual RGCs loss and vision function impairment. Such effect may be mediated through the regulation of p38 MAPK signaling pathway.